Direction and speed control of DC motor - Norfadilah, Zulkefli (2012)
Direct current motor is an important drive configuration for many applications across a wide range of powers and speeds. It have variable characteristics and used extensively in variable-speed drives. The goals of this project are to control the direction and speed of Direct Current (DC) motor. The Radio Frequency (RF) modules also used to make this project as a user friendliness to control the interface yet make it more useful. This project divided into two part of circuit. First circuit is for transmitter and another circuit is for the receiver. Pulse Width Modulation (PWM) technique is used where its signal is generated by PIC 18F4550. The PWM signal will send to the motor driver to vary the voltage supply to the motor in a desired speed. The DC Motor driver L293D is used in this project as it is a component that has dual full bridge driver where it also can control the direction of the DC motor. A rotary encoder plate is coupled to the end of motor shaft to provide the feedback speed signal to the controller. The RF modules used here are NT-T10A for transmitter module and CWC-12 for the receiver module. Four push buttons are built at the transmitter side as switches to control the speed and direction of DC motor. The four switches are interfaced to the RF transmitter module through PIC 18F4550. 16 x 2 Liquid Crystal Display (LCD) Modules is added at receiving side. It functions to display the outputs or corresponding action that obtain from the PIC 18F4550. In conclusion, the direction and speed of DC motor can be controlled. Plus, this motor controller can be applied as a basis in roboting system, kid’s toys and also industrial field.